ALMA-IMF, X : The core population in the evolved W33-Main (G012.80) protocluster - Armante, M. (2024)
Context. One of the central questions in astrophysics is the origin of the initial mass function (IMF). It is intrinsically linked to the processes from which it originates, and hence its connection with the core mass function (CMF) must be elucidated.Aims: We aim to measure the CMF in the evolved W33-Main star-forming protocluster to compare it with CMF recently obtained in other Galactic star-forming regions, including the ones that are part of the ALMA-IMF program.Methods: We used observations from the ALMA-IMF large programme: ~2´ × 2´ maps of emission from the continuum and selected lines at 1.3 mm and 3 mm observed by the ALMA 12m only antennas. Our angular resolution was typically 1″, that is, ~2400 au at a distance of 2.4 kpc. The lines we analysed are CO (2-1), SiO (5-4), N2H+ (1-0), H41α as well as He41α blended with C41α. We built a census of dense cores in the region, and we measured the associated CMF based on a core-dependent temperature value.Results: We confirmed the `evolved´ status of W33-Main by identifiying three H II regions within the field, and to a lesser extent based on the number and extension of N2H+ filaments. We produced a filtered core catalogue of 94 candidates that we refined to take into account the contamination of the continuum by free-free and line emission, obtaining 80 cores with masses that range from 0.03 to 13.2 M⊙. We fitted the resulting high-mass end of the CMF with a single power law of the form N(log(M)) ∝ Mα, obtaining α = −1.44−0.22+0.16, which is slightly steeper but consistent with the Salpeter index. We categorised our cores as prestellar and protostellar, mostly based on outflow activity and hot core nature. We found the prestellar CMF to be steeper than a Salpeter-like distribution, and the protostellar CMF to be slightly top heavy. We found a higher proportion of cores within the H II regions and their surroundings than in the rest of the field. We also found that the cores´ masses were rather low (maximum mass of ~13 M⊙).Conclusions: We find that star formation in W33-Main could be compatible with a `clump-fed´ scenario of star formation in an evolved cloud characterised by stellar feedback in the form of H II regions, and under the influence of massive stars outside the field. Our results differ from those found in less evolved young star-forming regions in the ALMA-IMF program. Further investigations are needed to elucidate the evolution of late CMFs towards the IMF over statistically significant samples.